Persepsi Mahasiswa KPI UIKA terhadap Desain Komunikasi Visual pada Akun @HIMAKPI_UIKA - Fairuz, Muhammad Afnan; M. Dahlan R (Komunika: Journal of Communication Science and Islamic Dakwah, 2025)
The research on the perception of students of Islamic Broadcasting Communication (KPI) at Universitas Ibn Khaldun Bogor (UIKA) towards the design of visual communication on the @himakpi_uika account is a study aimed at determining how students evaluate and respond to a visual design object in communication. This research is very important for design professionals, as it helps them understand how their visual design is accepted by the audience. The method used in this research is qualitative, with the researcher using a field study approach combined with data reduction techniques to analyze and interpret the collected information. The results of the research conducted showed that KPI students have a positive perception of the @himakpi_uika Instagram account. They consider the design of the account to clearly distinguish between the Himpunan Mahasiswa (Hima) KPI Instagram account and other study programs at UIKA and to demonstrate professionalism. In addition, they also consider the account capable of contributing and being a trustworthy and useful source of information. Students particularly appreciate the way the design reflects the identity and values of the Hima KPI program, as it provides both aesthetic appeal and functional communication. Each student has a different reason for following the account, such as seeking information, evaluating designs that are attractive and creative, and wanting to know the activities and values of da’wah contained in the account. The study further reveals how students perceive the role of visual design in reinforcing the image of the institution, influencing student engagement, and promoting relevant content effectively.